2022
DOI: 10.1186/s12984-022-01085-5
|View full text |Cite
|
Sign up to set email alerts
|

Criterion validity of ActiGraph monitoring devices for step counting and distance measurement in adults and older adults: a systematic review

Abstract: Background Wearable activity monitors such as ActiGraph monitoring devices are widely used, especially in research settings. Various research studies have assessed the criterion validity of ActiGraph devices for step counting and distance estimation in adults and older adults. Although several studies have used the ActiGraph devices as a reference system for activity monitoring, there is no summarized evidence of the psychometric properties. The main objective of this systematic review was to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 66 publications
4
21
0
Order By: Relevance
“…All approaches to assess musculoskeletal fitness and physical functioning have demonstrated excellent validity (ICC > 0.90) and/or reproducibility (r > 0.75) [ 19 , 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…All approaches to assess musculoskeletal fitness and physical functioning have demonstrated excellent validity (ICC > 0.90) and/or reproducibility (r > 0.75) [ 19 , 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Steps/d were determined by calculating steps for each 15‐seconds epoch using ActiLife's proprietary algorithm and dividing the total number of steps by the number of adherent wear days 17,25 . A systematic review suggested that the GT3X+ has good criterion validity 26 . Steps/d are a straightforward metric of movement that can be clearly translated into public health recommendations 27 .…”
Section: Methodsmentioning
confidence: 99%
“…17,25 A systematic review suggested that the GT3X+ has good criterion validity. 26 Steps/d are a straightforward metric of movement that can be clearly translated into public health recommendations. 27 Light intensity steps/d were those taken during 15-seconds epochs assigned to LPA while MV steps were those taken during 15-seconds epochs assigned to MVPA.…”
Section: Accelerometer Measures Of Pa and Sbmentioning
confidence: 99%
“…32 Physical activity and sedentary time were assessed using an activity sensor (Actigraph GT3x accelerometer). The Actigraph GT3x accelerometer has been shown to be valid 33 and reliable 34 for the measurement of PA in adults and older adults. The hip-worn Actigraph GT3x accelerometer has better accuracy for detecting steps during walking as compared with if the device is worn at the wrist.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…The hip-worn Actigraph GT3x accelerometer has better accuracy for detecting steps during walking as compared with if the device is worn at the wrist. 33 The validity of Actigraph GT3x to measure steps has also been validated in PwPD. 35 Participants were instructed to wear the accelerometer on the hip for 7 consecutive days.…”
Section: Outcome Measuresmentioning
confidence: 99%